If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 = 2(-3 + -8n) + 5(4 + 5n) -4 = (-3 * 2 + -8n * 2) + 5(4 + 5n) -4 = (-6 + -16n) + 5(4 + 5n) -4 = -6 + -16n + (4 * 5 + 5n * 5) -4 = -6 + -16n + (20 + 25n) Reorder the terms: -4 = -6 + 20 + -16n + 25n Combine like terms: -6 + 20 = 14 -4 = 14 + -16n + 25n Combine like terms: -16n + 25n = 9n -4 = 14 + 9n Solving -4 = 14 + 9n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-9n' to each side of the equation. -4 + -9n = 14 + 9n + -9n Combine like terms: 9n + -9n = 0 -4 + -9n = 14 + 0 -4 + -9n = 14 Add '4' to each side of the equation. -4 + 4 + -9n = 14 + 4 Combine like terms: -4 + 4 = 0 0 + -9n = 14 + 4 -9n = 14 + 4 Combine like terms: 14 + 4 = 18 -9n = 18 Divide each side by '-9'. n = -2 Simplifying n = -2
| 3(-8)+2-5(-8)=-14 | | -6x+36=3(3x-8) | | 2(x+3)+2=5x-7 | | 23w-w^2-126=0 | | 5a/6-7/12+3a=21/6 | | 3(7n+5)+6(n+6)=24 | | 8y-5=6y-18 | | -3.3e=-3.74 | | 11z+8y= | | 5x^2-10x+7=0 | | -12x-8=2x-2 | | 2x+2-3x=5 | | 5x-51=110-2x | | 3(-5p-1)+6(1+6p)=66 | | (n+15)/5 | | (n+15)/5 | | 2x^2=10x+24 | | 93+7x=51-2x | | 11x-33=9x+11 | | 12=3z+9 | | -14=4-(9x-1) | | (15x+5)=86+6x | | -22=3(2-7x)+7(-7x+6) | | 4x+8=4x+4 | | 7f=140 | | 378=(32+2x)(29+2x) | | (n+15)/15 | | 5x+14+3x-8=10x-24 | | 1/125=25^3x+2 | | 2ax=-a | | 5-1=n | | M=1m+px |